Anamnestic Immune Response and Safety of an Inactivated Quadrivalent Influenza Vaccine in Primed Versus Vaccine-Naïve Children. Issue 2 (February 2019) - Claeys, Carine; Chandrasekaran, Vijayalakshmi; García-Sicilia, José; Prymula, Roman; Díez-Domingo, Javier; Brzostek, Jerzy; Marès-Bermúdez, Josep; Martinón-Torres, Federico; Pollard, Andrew J.; Růžková, Renata; Carmona Martinez, Alfonso; Ulied, Angels; et al.
Abstract : Background: It has not yet been demonstrated whether 2 doses of inactivated quadrivalent influenza vaccine (IIV4) prime a booster response in infants. We evaluated the anamnestic immune response to an IIV4 in children 17−48 months of age. Methods: Children were randomized to 2 doses of IIV4 or control in the primary phase III study (NCT01439360). One year later, in an open-label revaccination extension study (NCT01702454), a subset of children who received IIV4 in the primary study (primed group) received 1 IIV4 dose and children who received control in the primary study (unprimed) received 2 IIV4 doses 28 days apart. The primary objective was to evaluate hemagglutination inhibition (HI) antibody titers 7 days after first IIV4 vaccination in the per-protocol cohort (N = 224 primed; N = 209 unprimed). Neutralizing and antineuraminidase antibodies were also measured. Safety was analyzed in the total vaccinated cohort (N = 241 primed; N = 229 unprimed). Results: An anamnestic response was observed in primed children relative to unprimed controls, measured by age-adjusted geometric mean HI titer ratios against strains homologous (A/H1N1: 9.0; B/Victoria: 3.9) and heterologous (A/H3N2: 2.7; B/Yamagata: 6.7) to those in the primary vaccination series. The anamnestic response in primed children included increases in neutralizing antibodies (mean geometric increase: 5.0–10.6) and antineuraminidase antibodies (4.9–8.8). No serious adverse events related to vaccination were reported. Conclusions: In this study, 2-dose priming with IIV4 induced immune memory that was recalled with 1-dose IIV4 the following year to boost HI, antineuraminidase and neutralizing antibodies, even though the IIV4 strain composition partially changed. Abstract : Supplemental Digital Content is available in the text.